Potential Antibacterial Activity of Moringa Leaf (Moringa oleifera) against Staphylococcusaureus and Porphyromonasgingivalis: Rapid Review - Nurfauziah, Hilda; Susanto, Agus; Carolina, Dyah Nindita (European Journal of General Dentistry, 2025)
Periodontal disease is caused by plaque bacteria such as Staphylococcus aureus and Porphyromonas gingivalis, which play a major role in its progression. Standard treatment involves scaling and root planing, often combined with antibiotics as adjunct therapy. However, inappropriate antibiotic use may lead to resistance. Therefore, natural antibacterial agents with a lower risk of resistance, such as Moringa oleifera leaves, are of interest. This review aimed to evaluate the antibacterial potential of Moringaoleifera leaf extract against S. aureus and P. gingivalis.This study used the rapid review method. Article searches were conducted on four databases (PubMed, Scopus, EBSCOHost, and SpringerLink) as well as through manual searches. Questions for this study were organized according to PICO-focused principles and Preferred Reporting Items for Systematic Reviews and Meta-Analyses analysis was used. The types of articles used were English and Bahasa Indonesia articles with the type of in vitro research published in 2014 to 2024. The data in the articles included inhibition zone diameter and minimum inhibitory concentration.A total of eight articles were obtained, which showed the antibacterial activity of Moringa oleifera leaf extract against S. aureus and P. gingivalis, as indicated by the inhibition zone diameters and minimum inhibitory concentrations.Based on this review, it can be concluded that Moringa oleifera leaf extract has proven antibacterial potential against S. aureus and P. gingivalis, with varying results influenced by the type of solvent and extract concentration.
Keywords: antibacterial; Moringa oleifera; periodontal disease; Porphyromonas gingivalis; Staphylococcus aureus